Utilization of Coal Bottom Ash and Cattle Manure as Soil Ameliorant on Acid Soil and Its Effect on Heavy Metal Content in Mustard (Brassica juncea) - Agustini, Rika Yayu; Iskandar, Iskandar; Sudarsono, Sudarsono; Jaswadi, Jaswadi; Wahdaniyah, Gusti (UNIVERSITY OF LAMPUNG, 2017)
Coal bottom ash and cattle manure can be used as soil ameliorant. The application of coal bottom ash and cattle manure can improve the soil chemical properties, such as pH and the amounts of available nutrients in soil. The objective of the study was to understand the effect of coal bottom ash and cow manure application on soil chemical properties and heavy metal contents in soil and mustard (Brassica juncea).Â A pot experiment was conducted in a greenhouse, including three treatment factors, i.e. age of coal bottom ash (fresh, 4 months and 2 years), dose of coal bottom ash, i.e. 0, 40 and 80 Mg ha-1, and dose of cattle manure, i.e. 0 and 10 Mg ha-1. The results show that the application of coal bottom ash and cattle manure increased the pH and the amounts of total-N, available-P and exchangeable cations (K, Ca and Mg) of the soil. The application of coal bottom ash increased the amounts of Pb, Cd and Co in the soil, but did not increase the amounts of Pb and Co in mustard, while the application of cattle manure increased the amount of Cd both in soil and mustard.Â Â Keywords: Coal bottom ash, cattle manure, heavy metal, mustard, soil ameliorant